Associations between musical abilities and precursors of reading in preschool aged children - Degé, Franziska; Kubicek, Claudia; Schwarzer, Gudrun (Frontiers in Psychology, 2015)
The association between music and language, in particular, the overlap in their processing results in the possibility to use one domain for the enhancement of the other. Especially in the preschool years music may be a valuable tool to train language abilities (e.g., precursors of reading). Therefore, detailed knowledge about associations between musical abilities and precursors of reading can be of great use for designing future music intervention studies that target language-related abilities. Hence, the present study investigated the association between music perception as well as music production and precursors of reading. Thereby, not only phonological awareness, the mostly studied precursor of reading, was investigated, but also other precursors were examined. We assessed musical abilities (production and perception) and precursors of reading (phonological awareness, working memory, and rapid retrieval from long-term memory) in 55 preschoolers (27 boys). Fluid intelligence was measured and controlled in the analyses. Results showed that phonological awareness, working memory, and rapid retrieval from long-term memory were related to music perception as well as to music production. Our data suggest that several precursors of reading were associated with music perception as well as music production.